LITERATURE-BASED EXTENSIVE READING ACCOMPANIED BY READING LOGS: A CASE FOR DEVELOPING CRITICAL THINKING SKILLS OF ENGLISH LITERATURE STUDENTS - Khonamri, Fatemeh; Farzanegan, Masoumeh (International Journal of Education, 2016)
This study attempted to examine the effects of an ER program accompanied by reading logs on the degree of critical thinking skills of sophomore English literature students at the University of Mazandaran. Two groups of English Literature majors formed the two experimental groups of the study in which only the former kept guided reading logs, while the latter group only read extensively.Â  Participants were also divided by their proficiency in reading into two groups of high and low achievers to compare the differences, if any, in the critical thinking skills observed. The results of the Independent t-test indicated no significant difference between the groups regarding their critical thinking ability (sig= .900). Thus, it was concluded that although both groups showed a little progress after the treatment, the difference was not statistically significant whereupon to conclude that reading logs may not drastically affect learners' critical thinking development.